The Role of Proton Transfer on Mutations - Srivastava, Ruby (Frontiers in Chemistry, 2019)
Hydrogen bonds play a critical role in nucleobase studies as they encode genes, map protein structures, provide stability to the base pairs, and are involved in spontaneous and induced mutations. Proton transfer mechanism is a critical phenomenon that is related to the acid–base characteristics of the nucleobases in Watson–Crick base pairs. The energetic and dynamical behavior of the proton can be depicted from these characteristics and their adjustment to the water molecules or the surrounding ions. Further, new pathways open up in which protonated nucleobases are generated by proton transfer from the ionized water molecules and elimination of a hydroxyl radical in this review, the analysis will be focused on understanding the mechanism of untargeted mutations in canonical, wobble, Hoogsteen pairs, and mutagenic tautomers through the non-covalent interactions. Further, rare tautomer formation through the single proton transfer (SPT) and the double proton transfer (DPT), quantum tunneling in nucleobases, radiation-induced bystander effects, role of water in proton transfer (PT) reactions, PT in anticancer drugs–DNA interaction, displacement and oriental polarization, possible models for mutations in DNA, genome instability, and role of proton transfer using kinetic parameters for RNA will be discussed.